Association between nephropathy and QT dispersion in type 2 diabetic patients - Oluk, Beyza (Journal of Surgery and Medicine, 2019)
Aim: Due to increased diabetes and diabetes-related mortality all over the world, the importance of appropriate and readily available screening tests for diabetic patients is increasing. In this study, we investigated the relationship between urine protein/creatinine ratio and QT dispersion. We aimed to determine the association between nephropathy and autonomic neuropathy, the two significant complications of diabetes, through simple and achievable tests. Methods: We retrospectively evaluated the medical records of 45 male and 50 female patients, who were attended at diabetes outpatient clinic with a diagnosis of type 2 diabetes in one month period. A 12-lead electrocardiogram (ECG), HbA1 and glucose levels were evaluated. Urinary protein/creatinine ratios (P/K) were measured at spot intervals. ECGs were transferred to the computer environment, and QT intervals were calculated and corrected for the patient’s heart rate using Bazett’s formula. QT-max (longest QT interval), QT-min (shortest QT interval) and QT-dispersion analyzes were performed in two groups, in all patients by excluding those with ischemic heart disease. The threshold value for proteinuria detection was 91 mg/g. Spot urine protein/creatinine ratio of less than 91mg/g was accepted as normal, and those with over 91mg/g were classified as proteinuric. Results: The mean QT-min (388.50 ± 27.28 ms), QT-max (441.25 ± 29.76 ms) and QT dispersion (52,74 ± 16,80 ms) were significantly higher than the reference values in both groups-in all patients by excluding those with ischemic heart disease. When all cases and those with ischemic heart disease were excluded, QT dispersion value was higher in patients with proteinuria (those with urine P/K levels 91 mg/g and above). This difference was not statistically significant. (p> 0.05) In this study, we found that QT durations were long independent of cardiovascular disease in diabetic patients, but not associated with protein/creatinine ratio Conclusion: As a result, in this study, we examined the relationship between spot urine protein/creatinine ratio and QT intervals in diabetic patients, and we did not find a significant association between the two parameters. Although there have been studies in the literature showing that there is a relationship between albumin/creatinine ratio and QT intervals, we could not find an association with P/K ratio.